Efecto de la ivermectina y aceite de molle (Schinus molle) en el tratamiento de sarna sarcóptica inducida en ratones de laboratorio Huánuco, 2013 - Martel Tolentino, Wilder (2017)
The objective of this research was evaluate the effect of ivermectin and oil molle in the treatment the sarcoptic scabies induced in mice, Huánuco 2013. It was held an experimental, comparative, and longitudinal study was conducted. The study population was composed of a total of 20 laboratory of the strain BALB/c mice (Mus musculus).The research was conducted in the laboratory of the Facultad de Medicina Veterinaria y Zootecnia of the Universidad National Hermilio Valdizán of Huánuco, during the period April to August 2013. Observation guides were used to collect data. Standard deviation and the Student T test were used to the inferential analysis of the results. Our study found three symptoms and signs of scabies that are: Erythema, pruritus and alopecia. Mean time to cure sarcoptic of laboratory mice using oil of molle (Schinus molle) had a mean of 12.3 days and in the control group (ivermectin) was 13.7 days; It is statistically significant with P≤0, 000. Finally it is concluded that using molle oil scabies sarcoptic mange will heal more quickly and therefore is different and better than ivermectin. Within the signs and symptoms of scabies sarcoptic mange in laboratory mice treated with oil of molle (Schinus molle) as: Erythema (P≤0. 000); pruritus (P≤0. 000) and alopecia (P≤0, 000) were statistically significant.